Efforts in improvement of nuclear knowledge and information management in Croatia. (30th September 2005) - Pleslic, Sanda; Novosel, Nevenka
The IAEA was authorised for exchange of technical and scientific information on peaceful uses of atomic energy and established INIS in 1970 as an international bibliographic database in the nuclear field and in nuclear related areas. Countries at different levels of technological development could derive benefits from INIS output products. The use of nuclear technology relies on the accumulation of knowledge in nuclear science and technology, including both technical information in documents and databases, and knowledge in human resources. Nuclear knowledge and information exchange are important for the process of decision-making. The IAEA supports all Members in systematic knowledge preservation and information exchange, who want to transfer their practical experience to the younger generation and to archive important information. Croatia is involved in activities in knowledge and information management since 1994 when she joined INIS. Thanks to development and application of new information technologies within the INIS information management framework, Members improve the collection, production and dissemination of nuclear knowledge and information.